An industry case study of micro component design and semantic mediation. (14th July 2008) - Wu, Raymond
This paper is a case study of enterprise integration in financial industry which consists of two parts. The first is component based design, and the second is semantic mediation. It explains why componentisation and semantics are both critical. This research paper uses examples in the industry to demonstrate component-based implementation and semantics mediation. To investigate the fundamental mechanism for the further understanding of the meaning of semantic mediation, we execute benchmarking by using both empirical experiments and theoretical modelling. Our observations show that a significant enhancement can be achieved by using the mediation strategy in semantic metadata.